Post-mortem interval estimation in a forensic case with two predatory species: Chrysomya albiceps and Synthesiomyia nudiseta / Tania Ivorra, Anabel Martínez-Sánchez and Salvador Giner Alberola - Ivorra, Tania; Martínez-Sánchez, Anabel; Alberola, Salvador Giner (Faculty of Medicine, 2021)
Introduction: Forensic entomology is the utilization of arthropod science in legal practice. Blow flies (Diptera: Calliphoridae) are a prevalent family in medicolegal investigations due to their colonization of vertebrates, including living or deceased humans. Longevity of insects associated with legal investigations is an important life-history trait that could be useful in determining a minimum time of colonization (TOC) interval. Lucilia eximia (Wiedemann) (Diptera: Calliphoridae) is known to colonize remains and cause myiasis; however, this species is understudied. The purpose of this study was to investigate the longevity of L. eximia adults with and without resources. Methods: Lucilia eximia adults were placed in six different mesh cages at a 1:1 sex ratio, where flies in three cages were fed and provided water, while those in the remaining cages were not. Cages were placed in a walk-in incubator set to 24°C, 60% RH, and a 14:10 L:D. Mortality was recorded daily. Results: Males and females did not live significantly longer than each other within either treatment. Life span of adults provided resources was 58.41 ± 27.79 d, while deprived individuals lived 1.61 ± 0.49 d. Rate of mortality was nearly 6X greater for those deprived of food and water than those provided such resources. Conclusions: Access to food and water impacted adult longevity. Forensic entomologists could potentially estimate time since adult emergence based on mortality proportion of adults present in relation to environmental conditions and access to food in an enclosed environment (e.g., building). However, such a method will need to be validated.